2020
DOI: 10.3389/fpsyg.2020.01501
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Presumed Infection Routes and Psychological Impact on Staff in Administrative and Logistics Departments in a Designated Hospital in Wuhan, China

Abstract: The baseline, job before diagnosis, presumed infection environment, use of protective equipment, and psychological status before and after diagnosis were collected and analyzed. A total of 18 uninfected staff members working alongside them in the same environment and 18 random matched infected doctors and nurses formed two control groups; the psychological impact of these three groups was then compared. Results: Of the 18 members of staff, 88.89% were infected due to the working environment (hospital), and nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…While frontline HCWs are most impacted by the psychosocial risks and related negative health outcomes, the body of evidence reviewed shows that the mental health of all workers in the whole healthcare system can be impacted due to new policies and procedures and the risk of infection, including nurses and doctors in their usual hospital wards [ 52 ], ophthalmologists [ 53 ] medical imaging professionals [ 54 ], and nonmedical personnel, such as allied health professionals, pharmacists, technicians, administrators, clerical staff, and maintenance workers [ 55 , 56 ], as well as community-based nurses [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…While frontline HCWs are most impacted by the psychosocial risks and related negative health outcomes, the body of evidence reviewed shows that the mental health of all workers in the whole healthcare system can be impacted due to new policies and procedures and the risk of infection, including nurses and doctors in their usual hospital wards [ 52 ], ophthalmologists [ 53 ] medical imaging professionals [ 54 ], and nonmedical personnel, such as allied health professionals, pharmacists, technicians, administrators, clerical staff, and maintenance workers [ 55 , 56 ], as well as community-based nurses [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides enhancing mental health by reducing anxiety and depression, evidence has showed that religious coping could help in stress management [ 36 ] and traumatic experiences [ 37 ], such as in the face of this arduous pandemic. In addition, a study in China revealed that 77.8% of the hospital staff members who were infected with COVID-19 experienced psychological distress [ 38 ], hence warranting the need of psychological interventions. Therefore, HCWs diagnosed with COVID-19 will also benefit from religious coping, which enhances coping with medical illnesses, modifies psychological reactions to illness, cultivates social support and aids in making meaning in life [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the hours spent in the hospital, it is known that long duty hours (15 hours or more per day) are also associated with increased risk of infection in healthcare workers [ 14 ]. In one study, almost 45% of COVID-19 infected health care workers reported working more than 7 hours/day [ 11 ].…”
Section: Discussionmentioning
confidence: 99%